Higher risk of hydraulic dysfunction and carbohydrate depletion of declining Larix principis-rupprechtii trees - Huanhuan Song; Tianyu Zhong; Jianxiao Zhu; Tao Yan (Ecological Processes)
Abstract Background Climate change associated with droughts has led to widespread forest decline. Hydraulic and carbon-related performances are key physiological processes for the tolerance of trees to environmental changes, yet our current understanding of such physiological performances for forest decline is still limited. Here, we investigated the hydraulic and carbohydrate performances of healthy and declining (canopy dieback) trees in temperate larch (Larix principis-rupprechtii) plantations. Results Relative to healthy trees, the higher native percentage loss of xylem hydraulic conductivity and lower xylem hydraulic conductivity indicated a deterioration of the integrity of the hydraulic system in declining trees. Additionally, the comparable Huber value, intrinsic water-use efficiency, and leaf mass per area between healthy and declining trees suggest a relatively profligate water-use strategy by declining trees. Declining trees had lower nonstructural carbohydrate concentrations in leaves, branches, and twigs but higher soluble sugars concentration in fine roots than conspecific healthy trees. Conclusions Overall, declining trees in larch plantations would be more vulnerable to drought due to the higher risk of hydraulic dysfunction and carbohydrate depletion.